Drought propagation in space and time: the role of groundwater flows. (1st September 2022) - Hellwig, J; Liu, Y; Stahl, K; Hartmann, A
Abstract: Droughts cause large economic and social impacts all over the world. During drought, groundwater maintains streamflow and can help to mitigate impacts. It governs how drought propagates through the hydrological cycle. Groundwater flows between topographic catchments may modify groundwater dynamics considerably and also influence groundwater's drought mitigation potential. In this study, we relate drought propagation times to quantitative estimates of groundwater gains or losses for a global set of catchments. For the majority of catchments there is no link found, however, for 16.5% of both groundwater gaining and groundwater losing catchments groundwater flow processes affect drought propagation. Influences of intercatchment groundwater flows (IGFs) on drought propagation are significantly related to catchment characteristics and abundant in North America, South America and Australia. As IGF mostly slow down drought propagation they may increase the potential of the system to buffer meteorological droughts. Reliable drought forecasting and proactive drought governance will benefit from better understanding major influences on drought propagation including IGFs.